Effects of insulin therapy optimization with sensor augmented pumps on glycemic control and body composition in people with cystic fibrosis-related diabetes - Grancini, V.; Alicandro, G.; Porcaro, L. L.; Zazzeron, L.; Gramegna, A.; Morlacchi, L. C.; Rossetti, V.; Gaglio, A.; Resi, V.; Daccò, V.; Blasi, F.; Orsi, E. (Frontiers in Endocrinology, 2023)
Objective. Cystic fibrosis (CF)-related diabetes (CFRD) resulting from partial-to-complete insulin deficiency occurs in 40-50% of adults with CF. In people with CFRD, poor glycemic control leads to a catabolic state that may aggravate CF-induced nutritional impairment and loss of muscle mass. Sensor augmented pump (SAP) therapy may improve glycemic control as compared to multiple daily injection (MDI) therapy. Research Design and Methods. This non-randomized clinical trial was aimed at evaluating the effects of insulin therapy optimization with SAP therapy, combined with a structured educational program, on glycemic control and body composition in individuals with insulin-requiring CFRD. Of 46 participants who were offered to switch from MDI to SAP therapy, 20 accepted and 26 continued the MDI therapy. Baseline demographic and clinical characteristics were balanced between groups using a propensity score-based overlap weighting procedure and weighted mixed effect regression models were used to estimate changes in study outcomes. Results. After 24 months changes in HbA1c were: -1.1 % (-12.1 mmol/mol) (95% CI: -1.5; -0.7) and -0.1 % (-1 mmol/mol) (95% CI: -0.5; 0.3) in the SAP and MDI therapy group, respectively, with a between-group difference of -1.0 (-10 mmol/mol) (-1.6; -0.5). SAP therapy was also associated with a decrease in mean glucose (between group difference: -32 mg/dL; 95% CI: -44; -19) and an increase in TIR (between group difference: 19.3%; 95% CI 13.9; 24.7) and in fat-free mass (between group difference: +5.5 Kg, 95% CI: 3.2; 7.8). Conclusions. Therapy optimization with SAP leads to a significant improvement in glycemic control, which is associated with amelioration of body composition.